Comorbidity burden and nonclinical factors associated with sinonasal cancer all‐cause mortality. (14th August 2019) - Desai, Premal B.; Bukatko, Aleksandr R.; Simpson, Matthew C.; Adjei Boakye, Eric; Greenberg, Jason W.; Ward, Greg M.; Walker, Ronald J.; Antisdel, Jastin L.; Osazuwa Peters, Nosayaba
Abstract : Objective: To describe comorbidity burden and nonclinical factors associated with all‐cause mortality of sinonasal cancer in the United States. Methods: The National Cancer Database (2004–2013) was queried for adult cases of sinonasal cancer (n = 10, 518). Outcome of interest was all‐cause mortality. Independent variables included comorbidity score and nonclinical factors such as age, gender, race, facility type, distance to facility, insurance, and income. Survival analysis was conducted via multivariable extended Cox regression with Heaviside adjustments. Results: Patients were mostly (79%), male (61%), and mean age of diagnosis was 63.5 years. Approximately one in five patients (18.7%) had a major comorbid condition (Charlson‐Deyo score ≥ 1) at diagnosis. After adjusting for clinical factors, increasing comorbidity score was associated with a corresponding increase in hazard of mortality (aHR comorbidity score of 1 = 1.25; 95% CI, 1.16, 1.35), (aHR score of 2+ = 1.61; 95%, CI 1.41, 1.83). Hazard of mortality was also associated with being male (aHR = 1.11; 95% CI, 1.04, 1.17); black (aHR = 1.13, 95% CI, 1.03, 1.24); uninsured (aHR = 1.45; 95% CI, 1.25, 1.68) or on Medicaid (aHR = 1.50; 95% CI, 1.33, 1.69); residence in zip codes with lower median income quartile (aHR < 30, 000 = 1.17; 95% CI, 1.06, 1.29); and treatment at community cancer programs (aHR = 1.14, 95% CI 1.01, 1.28). Conclusion: Comorbid disease is associated with all‐cause sinonasal cancer mortality, and after accounting for known clinical factors, significant differences in mortality persist based on disparity‐driven, nonclinical factors. Level of Evidence: NA Laryngoscope, 130:1443–1449, 2020